PEMURNIAN BIOGAS DENGAN SISTEM BERLAPIS MENGGUNAKANN Fe2O3, ZEOLIT SINTETIK DAN ZEOLIT ALAM - Muhammad Dienullah; Hendry Sakke Tira; Yesung Allo Padang (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Abstract: Biogas purification process aims to reduce biogas impurities such as carbon dioxide (CO2) and hydrogen sulfide (H2S) to obtain higher methane (CH4) concentration. Adsorption is one method for purifying biogas using solids. The research used 3 adsorbent materials such as natural zeolite mordenite, synthetic zeolite 3A and Fe2O3. To maximize the performance of natural zeolite as adsorbent, it is necessary to activate with NaOH solution which NaOH concentration used is 0%, 5%, and 15% NaOH and then they were activated by physical activation under heating treatment at 250oC for 4 hours. The best biogas purification result with natural zeolite activation mode was obtained at activation of 5% NaOH and followed by 15% and 0% NaOH. This is because activation using NaOH with 1-2N concentration (molarity) led to a macro pore size of the zeolite, more uniform, and the pores on the micro pore can be cleaned. After obtaining the best quality of natural zeolite, a study on the adsorbent ratio of adsorbent tubes obtained from the best results in Fe2O3, synthetic zeolite and natural zeolite (1: 1: 2) was observed because the ability of natural zeolite adsorption is better than of synthetic zeolite and Fe2O3. Therefore, the more natural zeolite in the adsorbent tube the better the refining result.